2016
DOI: 10.1371/journal.pgen.1006317
|View full text |Cite
|
Sign up to set email alerts
|

Neocentromeres Provide Chromosome Segregation Accuracy and Centromere Clustering to Multiple Loci along a Candida albicans Chromosome

Abstract: Assembly of kinetochore complexes, involving greater than one hundred proteins, is essential for chromosome segregation and genome stability. Neocentromeres, or new centromeres, occur when kinetochores assemble de novo, at DNA loci not previously associated with kinetochore proteins, and they restore chromosome segregation to chromosomes lacking a functional centromere. Neocentromeres have been observed in a number of diseases and may play an evolutionary role in adaptation or speciation. However, the conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 66 publications
(132 reference statements)
1
48
0
Order By: Relevance
“…'Centromere repositioning', that is, the movement of the centromere along the chromosome without marker order variation, was first given as a possible mechanism for karyotype evolution in a broad investigation of chromosomal evolution in 60 species of primates (Dutrillaux 1979). Over the past few decades, numerous studies have found evolutionary new centromeres in different lineages, including fungi, insects, birds, and mammals (O'Neill et al 2004;Marshall et al 2008;Rocchi et al 2012;Scott and Sullivan 2014;Schneider et al 2016;Burrack et al 2016;Tolomeo et al 2017). Some of the observed karyotype reshuffling may be due to the inheritance of neo-centromeres (Amor et al 2004) while some may be the product of successive pericentric inversions (Rocchi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…'Centromere repositioning', that is, the movement of the centromere along the chromosome without marker order variation, was first given as a possible mechanism for karyotype evolution in a broad investigation of chromosomal evolution in 60 species of primates (Dutrillaux 1979). Over the past few decades, numerous studies have found evolutionary new centromeres in different lineages, including fungi, insects, birds, and mammals (O'Neill et al 2004;Marshall et al 2008;Rocchi et al 2012;Scott and Sullivan 2014;Schneider et al 2016;Burrack et al 2016;Tolomeo et al 2017). Some of the observed karyotype reshuffling may be due to the inheritance of neo-centromeres (Amor et al 2004) while some may be the product of successive pericentric inversions (Rocchi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Neocentromeres are previously naïve chromatin regions that give rise to functional kinetochores competent for chromosome segregation. Upon inactivation or deletion of the original centromeres, Candida neocentromeres form almost anywhere on the chromosome, though there is some preference for transcriptionally silent pericentric and subtelomeric regions [43, 210212]. Like in S. cerevisiae , centromeres and neocentromeres in Candida interfere with transcription of nearby genes [210], also suggesting heterochromatin characteristics.…”
Section: Chromosome Landmarks: Origins Telomeres and Centromeresmentioning
confidence: 99%
“…Upon inactivation or deletion of the original centromeres, Candida neocentromeres form almost anywhere on the chromosome, though there is some preference for transcriptionally silent pericentric and subtelomeric regions [43, 210212]. Like in S. cerevisiae , centromeres and neocentromeres in Candida interfere with transcription of nearby genes [210], also suggesting heterochromatin characteristics. The role of histone modifications for centrochromatin in Candida is unresolved; like S. cerevisiae, Candida lacks the conserved heterochromatin pathways that rely on methylation of H3K9 and H3K27.…”
Section: Chromosome Landmarks: Origins Telomeres and Centromeresmentioning
confidence: 99%
“…Neocentromeres are previously naïve chromatin regions that give rise to functional kinetochores competent for chromosome segregation. Upon inactivation or deletion of the original centromeres, Candida neocentromeres form almost anywhere on the chromosome, though there is some preference for transcriptionally silent pericentric and subtelomeric regions [43,[210][211][212]. Like in S. cerevisiae, centromeres and neocentromeres in Candida interfere with transcription of nearby genes [210], also suggesting heterochromatin characteristics.…”
Section: Author Manuscriptmentioning
confidence: 99%